2017
DOI: 10.7197/223.v39i32356.369336
|View full text |Cite
|
Sign up to set email alerts
|

The role of mean platelet volume, platelet distribution width and platelet / lymphocyte ratio in development of cerebral venous thrombosis

Abstract: SUMMARYObjective: Mean platelet volume (MPV) and platelet distribution width (PDW) are parameters that indicate platelet volume. It is assumed that large platelets are enzymatically and metabolically more active than small platelets. The relationship between elevated MPV and PDW values and arterial thrombosis has been demonstrated, but their roles in venous thrombosis are not fully understood. While the platelet / lymphocyte ratio (PLR), which is considered to be an inflammatory indicator, is known to be assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
0
6
0
2
Order By: Relevance
“…Recently, it has been showed that, the changes of lymphocyte count, subtypes of leukocytes, is associated with both cardiovascular diseases and other neurological diseases 13 . Lymphocytes have a controversial role in the inflammation after AIS.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been showed that, the changes of lymphocyte count, subtypes of leukocytes, is associated with both cardiovascular diseases and other neurological diseases 13 . Lymphocytes have a controversial role in the inflammation after AIS.…”
Section: Discussionmentioning
confidence: 99%
“…These cytokines contribue to the development of atherosclerosis via stimulating smooth muscle and interstitial cell proliferation. Additionally, the lymphocyte count changes has been revelaed to be related to both cardiovascular diseases and other neurological diseases 18 .…”
Section: Discussionmentioning
confidence: 99%
“…This diagnostic case includes heterogeneity among any could-be pathogenetic factors, even derived from noncardiac effects. The most notorious one is impaired endothelium in the collateral coronary circulation [8,9].…”
Section: Discussionmentioning
confidence: 99%